2023
DOI: 10.1002/anie.202313886
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Electrolyte Cations Dependent Kinetics on CoOOH‐Catalyzed Oxygen Evolution Reaction

Hongnan Jia,
Na Yao,
Can Yu
et al.

Abstract: The electrolyte cations‐dependent kinetics have been widely observed in many fields of electrocatalysis, however, the exact mechanism of the influence on catalytic performance is still a controversial topic of considerable discussion. Herein, combined with operando X‐ray diffraction (XRD) and high‐resolution transmission electron microscopy (HRTEM), we verify that the electrolyte cations could intercalate into the layer of pristine CoOOH catalyst during the oxygen evolution reaction (OER) process, while the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 50 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…(3) optimization of efficient and stable electrolyte systems, including electrolyte types (e.g., the electrolyte cations) and important parameters (e.g., pH value and composition of the electrolytes) [24][25][26][27]. However, OER in practical conditions exhibits remarkable complexity and remains inadequately understood, despite more than a century of study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) optimization of efficient and stable electrolyte systems, including electrolyte types (e.g., the electrolyte cations) and important parameters (e.g., pH value and composition of the electrolytes) [24][25][26][27]. However, OER in practical conditions exhibits remarkable complexity and remains inadequately understood, despite more than a century of study.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the sluggish kinetics of electrochemical OER hampers the widespread application of water electrolysis technology [6,7]. To date, substantial studies have been devoted to exploring efficient OER electrocatalysts, focusing on the subsequent three areas: (1) the design and optimization of catalysts with high OER efficiency, which play a crucial role in the OER reaction, including the exceptionally superior noble-metalbased metallic catalysts (such as IrO 2 and RuO 2 ) and some materials with unique electronic structures and chemical properties, such as cobalt-based and nickel-based catalysts, and so on [8][9][10][11][12][13][14][15][16][17]; (2) in-depth study of OER mechanisms and the detailed processes, including the formation and transformation of intermediates, as well as the reaction pathways and rate-determining steps, which have been revealed by utilizing advanced experimental techniques and theoretical calculations, thereby providing important theoretical foundations for guiding the design and optimization of catalysts [18][19][20][21][22][23]; (3) optimization of efficient and stable electrolyte systems, including electrolyte types (e.g., the electrolyte cations) and important parameters (e.g., pH value and composition of the electrolytes) [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…13h and i). 173 Similarly, Garcia et al indicated that larger cations (Cs + ) better stabilized NiOO–M + species. 174…”
Section: Engineering the Surface Microenvironment Of Electrocatalystsmentioning
confidence: 96%
“…Water electrolysis is often regarded as a highly promising and environmentally friendly method for producing hydrogen, as it does not release any carbon dioxide. [4][5][6] This is in stark contrast to conventional approaches such as steam reforming or coal gasification, which rely on the reaction between fossil fuels and steam. Nevertheless, the task of achieving high levels of efficiency in the large-scale synthesis of hydrogen utilizing renewable energy sources continues to pose significant challenges.…”
Section: Introductionmentioning
confidence: 99%